(untitled) (Research, Society and Development, 2022)
The present study aims to understand the main implications of syphilis in pregnant women with low socioeconomic status, characterize pregnant women diagnosed with syphilis, analyze the factors associated with syphilis in pregnant women, and present nursing actions to pregnant women diagnosed with syphilis during prenatal care. This is an integrative literature review, using three electronic databases: Latin American and Caribbean Health Sciences Literature (LILACS); Nursing Database (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE), using the following research question: What are the implications of syphilis in pregnant women with low socioeconomic status?. The analyzed studies reveal that the main difficulties regarding adherence to treatment and the reduction of vertical syphilis transmission are related to socioeconomic issues, infrastructure, in addition to the lack of knowledge on the part of health professionals. This high rate of involvement by congenital syphilis has several implications such as illness of the woman, malformation of the fetus, abortion or death of the baby or, when they are born, they are very sick. Therefore, specialized prenatal care is recommended.